Pengaruh Substitusi Pakan Komplit Komersial dengan Pakan Komplit Buatan Sendiri terhadap Kecernaan Protein dan Energi pada Babi Peranakan Landrace Fase Starter - Nena, Tresiana; Sembiring, Sabarta; Dodu, Tagu (Yayasan Sumber Daya Manusia Cerdas, 2025)
The purpose of this study was to determine the effect of replacing commercial complete feed with homemade complete feed on digestibility of energy and protein landrace crossbreed pigs in the starter phase. The material used was 12 landrace crossbreed pigs in starter phase aged 8-12 weeks with initial body weight of 6,5-15,6kg (CV=31,67%). This study used a Randomized Block Design (RBD) which consisted of 4 treatments with each treatment made 3 replications so that there were 12 experimental units. The treatments were P1: 100% commercial complete feed (CCF), P2: 50% commercial complete feed + 50% homemade complete feed (HCF), P3: 25% commercial complete feed + 75% homemade complete feed , P4: 100% homemade complete feed. The variables measured wer the consumption and digestibility of energy and protein. The data collected in this study were tabulated and analyzed using the analysis of variance. The results of statistical analysis showed that the treatment had significant effect (P<0,05) on protein consumption and no significant effect (P>0.05) on the energi consumption, digestibility of energy and digestibility of protein. It was concluded that the replacement of commercial complete feed with homemade complete feed had an effect on increasing energy consumption and protein consumption and gave the same results on energy and protein digestibility in starter phase pigs.